Association of income and health-related quality of life in atrial fibrillation. Issue 1 (11th April 2019) - Guhl, Emily; Althouse, Andrew; Sharbaugh, Michael; Pusateri, Alexandra M; Paasche-Orlow, Michael; Magnani, Jared W
Abstract : Objective: Health-related quality of life (HRQoL) is a patient-centred benchmark promoted by clinical guidelines in atrial fibrillation (AF). Income is associated with health outcomes, but how income effects HRQoL in AF has limited investigation. Methods: We enrolled a convenience cohort with AF receiving care at a regional healthcare system and assessed demographics, medical history, AF treatment, income, education and health literacy. We defined income as a categorical variable (<$20 000; $20 000–$49 999; $50 000–$99 999; >$100 000). We used two complementary HRQoL measures: (1) the atrial fibrillation effect on quality of life (AFEQT), measuring composite and domain scores (daily activity, symptoms, treatment concerns, treatment satisfaction; range 0–100); (2) the 12-item Short Form Survey (SF-12), measuring general HRQoL with physical and mental health domains (range 0–100). We related income to HRQoL and adjusted for relevant covariates. Results: In 295 individuals with AF (age 71±10, 40% women), we observed significant differences in HRQoL by income. Higher mean composite AFEQT scores were observed for higher income groups: participants with income <$20 000 had the lowest HRQoL (n=35, 68.2±21.4), and those with income >$100 000 had the highest HRQoL (n=64, 81.9±17.0; p=0.04). We also observed a significant difference by income in the AFEQT daily activity domain (p=0.02). Lower income was also associated with lower HRQoL in the mental health composite score of the SF-12 (59.7±21.5, income <$20 000 vs 79.3±16.3, income >$100 000; p<0.01). Conclusion: We determined that income was associated with HRQoL in a cohort with prevalent AF. Given the marked differences, we consider income as essential for understanding patient-centred outcomes in AF.